A 16-bit parallel processing in a molecular assembly - Bandyopadhyay, Anirban (National Academy of Sciences, 2008)
A machine assembly consisting of 17 identical molecules of 2,3,5,6-tetramethyl-1–4-benzoquinone (DRQ) executes 16 instructions at a time. A single DRQ is positioned at the center of a circular ring formed by 16 other DRQs, controlling their operation in parallel through hydrogen-bond channels. Each molecule is a logic machine and generates four instructions by rotating its alkyl groups. A single instruction executed by a scanning tunneling microscope tip on the central molecule can change decisions of 16 machines simultaneously, in four billion (4(16)) ways. This parallel communication represents a significant conceptual advance relative to today's fastest processors, which execute only one instruction at a time.